Effects of land use and seasonality on stream water quality in a small tropical catchment: The headwater of Corrego Agua Limpa, Sao Paulo (Brazil) - Rodrigues, Valdemir [UNESP] (2018)
Stream water quality is controlled by the interaction of natural and anthropogenic factors over a range of temporal and spatial scales. Among these anthropogenic factors, land cover changes at catchment scale can affect stream water quality. This work aims to evaluate the influence of land use and seasonality on stream water quality in a representative tropical headwater catchment named as Corrego Agua Limpa (Sao Paulo, Brasil), which is highly influenced by intensive agricultural activities and urban areas. Two systematic sampling approach campaigns were implemented with six sampling points along the stream of the headwater catchment to evaluate water quality during the rainy and dry seasons. Three replicates were collected at each sampling point in 2011. Electrical conductivity, nitrates, nitrites, sodium superoxide, Chemical Oxygen Demand (DQO), colour, turbidity, suspended solids, soluble solids and total solids were measured. Water quality parameters differed among sampling points, being lower at the headwater sampling point (0 m above sea level), and then progressively higher until the last downstream sampling point (2500 m above sea level). For the dry season, the mean discharge was 39.5 l s(-1) (from April to September) whereas 113.0 l s(-1) were averaged during the rainy season (from October to March). In addition, significant temporal and spatial differences were observed (P < 0.05) for the fourteen parameters during the rainy and dry period. The study enhance significant relationships among land use and water quality and its temporal effect, showing seasonal differences between the land use and water quality connection, highlighting the importance of multiple spatial and temporal scales for understanding the impacts of human activities on catchment ecosystem services. (c) 2017 Elsevier B.V. All rights reserved.